Bifunctional Biphenyl-2-ylphosphine Ligand Enables Tandem Gold-Catalyzed Propargylation of Aldehyde and Unexpected Cycloisomerization - Li, Ting; Zhang, Liming (Journal of the American Chemical Society, 2018)
Despite extensive studies in gold catalysis, σ-allenylgold species have not been invoked as catalytic intermediates and their reactivities not studied. This work reports for the first time they are generated in situ and undergo nucleophilic addition to activated aldehydes in a bifunctional phosphine ligand-enabled gold catalysis. This development reveals a broad range of opportunities to achieve propargylic C–H functionalization for the first time under catalytic and mild conditions. The homopropargylic alcohols generated undergo ligand-enabled cycloisomerizations involving an unexpected silyl migration.